THE STUDY OF REACTIVE AND PERSONAL ANXIETY, QUALITY OF LIFE IN PATIENTS WITH DYSPEPSIA IN OUTPATIENT DEPARTMENT - E. G. Kunakbaeva; Ya. M. Vahrushev (SINAPS LLC, 2016)
Conducted  a comprehensive  examination  of patients  in the  outpatient department, including laboratory  and instrumental methods,  the  test of Spielberg-Hanina to determine  the level of anxiety, the SF 36 test to determine  the level of quality of life. The survey revealed a decline in the quality of life in patients  with dyspepsia, the indicators of psychological health in organic and functional dyspepsia is lower than in healthy people. The intensity of pain was higher in patients  with epigastric pain syndrome. Lower quality of life were in the group with organic lesions of the upper gastrointestinal tract. The results of the test of Spielberg-Hanin demonstrated high personal anxiety in patients with different types of dyspepsia in comparison with healthy group. The obtained results complement the clinical and pathogenetic information regarding the different kinds of dyspepsia.